STUDI KELAYAKAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) PT DEMPO SUMBER ENERGY BATANG PELANGAI GADANG PESISIR SELATAN - Rahman, Aldito; Bandri, Sepanur; Putra, Andi M Nur; Syofian, Andi; Anugrah, Anggun (Ensiklopedia of Journal, 2024)
This research conducts a reassessment of PT Dempo Sumber Energi MHP by testing the water discharge, head height, energy loss, and the amount of power that will be released by PT Dempo Sumber Energi MHP in order to get optimal results as planned by PT Dempo Sumber Energi MHP. This reassessment will conduct a feasibility study of the existing result quality system by comparing the results of the data obtained by the author with the applicable standards, and taking into account the value generated at the MHP. So that when later results are found that are not in accordance with what has been determined, the author can recommend that the expected results are appropriate and can help smooth the process at the company. Calculation of the mainstay discharge with the MOCK method which has an effective discharge of 17,43 m3 / sec, a head as high as 43.4 m from the dam to the turbine house door, this has an impact on energy loss of 0.13 m due to the slightly curved shape of the pipe mouth of 0.2 and also energy loss due to closure in the pipe of 0.48 m. The turbine used is a francis turbine which has a head range of 10 to 350. The power to be generated is 41.124,7 kW which loses energy from the recorded results of 571 which can occur at any time due to certain things. This becomes a variety of factors that cause a reduction in the output power generated at the MHP.